Express Rail Link Sdn Bhd / Nadhirah Aqilah Zulkefly - Zulkefly, Nadhirah Aqilah (Faculty of Business and Management, 2023)
Public transportation is one of the important sector that contribute to our economy growth. But to encourage people to commute by using public transport is not an easy task to do. According to World Bank in 2015, it is reported that the percentage of Malaysian who use public transport is only 17%, lower than Singapore and Hong Kong 62% and 89% respectively. Based on the study (Sze Siong, 2018), found that factors such as physical facility, information system, safety and security, train and ticket and responsiveness was the main factor affecting the user’s satisfaction in their journey when using the services. For example, in the survey 61.3% of the respondents are students. Therefore, the price can be a burden to them when commuting using the rail transport service, as we know the price rate is different according to journey destinations and the service providers. In another local study conducted by (Ismail, 2012), shows that factors such as frequency, comfortable travel experience, security on board and travel time, price, and punctuality can affect the customers satisfaction. Based on these factors, the most crucial factors are time and price. Customers can be easily frustrated if they pay for a higher price but the time management is not as good as they expected. This can lead to their dissatisfaction with the service quality. Another study conducted by (Khairul Baharein and Kamariah, 2013), shows the attitude of the customer service staff plays an important role in influencing customers satisfaction. The customers prefer friendly and smiley staff to assist them. In the same study shows, the facilities provided also is the main concern for the customers. Things such as poor signage, lighting and toilets needs to be improve to ensure customers are satisfy with the service. Another study by (L. Eboli, 2018), shows that there is strong relationship between the service provided and the overall service quality expectation by the customers. A study conducted by (Ahmad Nazrul Hakimi Ibrahim, 2019), found that the reasons why customers feel dissatisfies with the service was due to the price of the ticket as most of the user are from low income category, the punctuality of the scheduled train, and the efficiency at the ticket counter. This factor can influence the customers’ satisfaction towards the service. For example, when the train did not arrive on time as scheduled, this can affect the customers’ scheduled and led to dissatisfaction. Another recent study conducted by (Ahmad Nazrul Hakimi Ibraihim, 2020), shows there are nine factors that influence the users’ satisfaction towards the public transport service. The nine factors includes, availability of service (parking facilities, Frequency, network coverage, operating hours), accessibility of service (ease of transfer), ticket (ticket price, types of tickets), information availability (on board and at the stations), travel time (punctuality, access time, speed, waiting and transfer time), customer service (personnel behaviour and customer service), comfort (cleanliness, comfort, seating capacity, noise, temperature of the cabin, quality of vehicle), safety (on board and platform) and lastly is image (eco-friendly and image in customers view). These nine factors are crucial for the service providers in order to achieve or go beyond customers’ expectation. When the service providers able to surpass customers’ expectation, indirectly the customers will feel satisfy towards the service. The problem is how the service providers can meet the customers’ expectation in providing their needs as the satisfaction factors can be vary for each customers. For example, a customers does not want the temperature too cold and while the others want the temperature to be increase. This shows that the factors can be different in achieving customers’ satisfaction towards the service.